TINDAK TUTUR DIREKTIF DALAM ACARA KAJIAN USTAZ HANAN ATTAKI SHARING TIME PADA KANAL YOUTUBE DI BULAN SEPTEMBER 2024 - Silva Yuan Dwiputra; Abdoel Gafar; Uli Wahyuni (Universitas Batanghari, 2025)
Language plays a crucial role as a medium of communication that enables humans to express ideas, thoughts, and emotions. In spoken communication, utterances are not merely tools for conveying information but also serve as means to influence, persuade, and direct interlocutors toward certain actions. This study aims to analyze the forms and functions of directive speech acts found in Ustaz Hanan Attaki’s sermons on the “Sharing Time” program uploaded to his YouTube channel in September 2024. The research employs a descriptive qualitative method, with data obtained from the transcripts of three sermon videos. Data collection techniques included listening and note-taking, while analysis was carried out through identification, classification, and interpretation based on Searle’s theory of speech acts. The findings reveal five forms of directive speech acts: ordering, commanding, requesting, advising, and recommending. Each form serves specific communicative functions, including instructive, persuasive, educative, and motivational purposes. The study highlights how Ustaz Hanan Attaki’s communication style effectively combines religious preaching with persuasive strategies tailored to resonate with younger audiences. These findings contribute to the field of pragmatics by demonstrating how directive speech acts function within contemporary religious discourse, while also offering practical insights into the role of language in religious communication..